An effective interionic interaction in semi-infinite metal in the presence of external electrostatic field with taking into account the local field approximation - Markovych, B.; Zadvorniak, I. (My University, 2016)
An effective interionic potential in semi-infinite metal, which is located in the external electrostatic field is studied. An effect of the local field correction and the applied external electric field on the effective interionic potential is investigated. Дослiджено ефективний потенцiал мiжiонної взаємодiї в напiвобмеженому металi, який мiститься у зовнiшньому електростатичному полi. Дослiджено вплив на ефективний потенцiал мiжiонної взаємодiї поправки на локальне поле та напруженостi прикладеного зовнiшнього електростатичного поля.
Ефективна мiжiонна взаємодiя в напiвобмеженому металi за наявностi зовнiшнього електричного поля з урахуванням поправки на локальне поле
Keywords: effective interionic potential; electrostatic field; pseudopotential; semi-infinite metal; ефективний потенцiал мiжiонної взаємодiї; електростатичне поле; псевдопотенцiал; напiвобмежений метал; 530.145